2021
DOI: 10.25136/2409-8698.2021.12.37192
|View full text |Cite
|
Sign up to set email alerts
|

Nationally oriented automotive marketing in China

Abstract:   This article examines the specificity of formation of nationally oriented automotive marketing in China. The object of this research is the Chinese nationally oriented automotive marketing, while the subject is verbal and nonverbal means of its creation. Special attention is given to the analysis of the techniques of creating texts for nationally oriented automobile advertising in the Chinese language, in which multimodal means are used for the development of a positive image of the country and impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the past few years in China, supplies of late-season mandarins have increased, while demand has been sluggish, so prices have plummeted. In response to increasing prices, between 2016 and 2020, the area of land under cultivation for late-season mandarins in Sichuan province, a major producer of this fruit, rose from 1.6 to 2.3 million mu (from 106,666.7 to 153,333.3 ha) (Wang, 2021). This enlarged growing area quickly translated into higher yields.…”
Section: Benefits Of Agricultural E-commerce For Farmers In Kangyang ...mentioning
confidence: 99%
“…In the past few years in China, supplies of late-season mandarins have increased, while demand has been sluggish, so prices have plummeted. In response to increasing prices, between 2016 and 2020, the area of land under cultivation for late-season mandarins in Sichuan province, a major producer of this fruit, rose from 1.6 to 2.3 million mu (from 106,666.7 to 153,333.3 ha) (Wang, 2021). This enlarged growing area quickly translated into higher yields.…”
Section: Benefits Of Agricultural E-commerce For Farmers In Kangyang ...mentioning
confidence: 99%
“…The literature [6] used an ethnographic field survey research method to investigate the information needs of car buyers before they bought a car and worked with the information builder of the Ford website to improve the Ford website using the data collected; the literature [7] conducted an automotive website satisfaction index study to determine the role of automotive websites in driving brand loyalty and sales volume. The literature [8] used the University of Michigan American Consumer Satisfaction Index scoring method to evaluate the websites of six major automotive companies: Chevrolet, Chrysler, Ford, Honda, Nissan, and Toyota, and found that the Toyota website had the highest user satisfaction of the six websites tested, thus increasing the likelihood that users of the site would purchase a Toyota vehicle; the Nissan website had the worst online consumer satisfaction, and It was concluded that automotive websites add value to a company's marketing activities and increase the likelihood that consumers will buy a car.…”
Section: Introductionmentioning
confidence: 99%
“…Qing Ma and Hanita Hassan. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%